Administrative management of the principal and evaluation of the organizational climate. Juan Guerrero Quimper, landmark educational institution. Lima - Espinoza Vásquez, Guisella Esther (2025)
Global change and the advancement of countries are based on the coherence established between the administrative management function (variable 1) and the organizational climate (variable 2) in educational institutions. The purpose of this study is to evaluate the link between both variables at the Juan Guerrero Químper flagship school in Lima. Measures for planning, organizing, directing, and controlling are dimensions of variable 1, and variable 2 is comprised of: communicating, motivating, and participating. Methodologically, we employed quantitative scientific approaches and descriptive correlational design, a hypothetical-deductive method, a cross-sectional approach, and an ordinal level. Data were collected using a survey and a questionnaire with Likert-based response alternatives, which were validated by three experts for reliability using Cronbach's alpha coefficient. A study was conducted among 70 teachers. We employed descriptive and inferential statistical analysis to test hypotheses; Spearman's rho correlation coefficient was used. We conclude that there is a significant relationship (r = 0.854, p = 0.000) between effective administrative management and a favorable work environment at the Juan Guerrero Quimper flagship institution. Furthermore, the dimensions of each variable show similar behavior.